Čezmejne dnevne delovne migracije v slovenskem obmejnem prostoru - Zupančič, Jernej (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2003)
The paper deals with reasons, flows and consequences of daily crossborder commution from Slovenia across the "Schengen" border towards Austria and Italy, as well as from Croatia and Hungary to Slovenia. This form of international migration is an important phenomenon in the borderlands. In Slovenia, migration of working force has a long tradition, especially in surroundings of bigger urban centres. Following the results of field research work, done in years 2000 and 2001 (interviews with custom service and border police; questionarries among crossborder commutters; structural analyses of borderland on both sides of the border), more than 14.000 Slovenian (among them approximately 8.000 or 57 % in Italy and 6.000 or 43 % in Austria) and 2500 Croatian citizens cross the Slovenian-Italian and Slovenian-Austrian border because of work. Otherwise, Slovenia attracts approximately 8.000 dailycommuters from Croatia and Hungary. The most frequent border crossings are Gornja Radgona, Sentilj (both towards Graz and south Styria), Karavanke-tunnel (towards south Carinthia), Miren (local border crossing towards Gorizia and surrounding), Fernetiči, Škofije and Kozina (towards Triest in Italy), and finally border crossings Sečovlje, Obrežje, Ormož in Petisovci towards Croatia. During the spring and autumn period the number is much higher because of season-workers. Daily crossborder commuters take different works in households, farms, but it is possible to find them among better paid agents, bussiness-makers and technical intelligentsia. According to the comparison of results in 2000 and 2001, the percent of highly educated specialists and agents increased evidently. Daily crossborder commution has important socioeconomic, spatial, demographical and ethno-cultural effects on borderland on both sides of the border. After some years, crossborder commuters collect a lot of experience from both sides of the border. Through this, those people have better chances for intensification of further crossborder cooperation.
Keywords: Slovenia; Slovenija; obmejna območja; obmejno sodelovanje; human migration; migracije; delovna sila; delovne migracije; ekonomske migracije